Monoamine Oxidase Inhibitory Action of Chalcones: A Mini Review - Mathew, Bijo; Haridas, Abitha; Suresh, Jerad; E. Mathew, Githa; Uçar, Gülberk; Jayaprakash, Venkatesan (Central Nervous System Agents in Medicinal Chemistry, 2016)
Introduction: Chalcones are one of the major classes of naturally occurring compounds and have a vast significance in medicinal chemistry, presenting with a wide scope of pharmacological actions. Discussion: The present review focused our attention onto the monoamine oxidase inhibitory activity of natural and synthetic chalcones. The review also emphasises the structure-activity relationship studies and molecular recognition of chalcones towards MAO-A and B inhibition. Conclusion: Many of the studies clearly revealed that most of the chalcones showed selective, reversible and potent MAO-B inhibition compared to MAO-A. Recent studies also showed that heteroaryl-based chalcones are potent MAO-A inhibitors.
Keywords: Alzheimer' s disease